2015
DOI: 10.1080/17470218.2015.1012087
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive abilities required in time judgment depending on the temporal tasks used: A comparison of children and adults

Abstract: The aim of this study was to examine age-related differences in time judgments during childhood as a function of the temporal task used. Children aged 5 and 8 years, as well as adults, were submitted to 3 temporal tasks (bisection, generalization and reproduction) with short (0.4/0.8 s) and long durations (8/16 s). Furthermore, their cognitive capacities in terms of working memory, attentional control, and processing speed were assessed by a wide battery of neuropsychological tests. The results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 62 publications
(71 reference statements)
1
44
0
1
Order By: Relevance
“…Globally, the profile of sense of time skills as reported by teachers showed a stronger predictive power towards the time discrimination task, and around half of variance of this task was explained by questionnaires’ scores. Time discrimination is considered a less demanding task, in terms of general cognitive skills such as working memory and speed processing, and seems to be a more ‘pure’ measure of time processing, compared to time reproduction (Droit‐Volet, Wearden, & Zélanti, ). Therefore, it is possible that the Sense of Time Questionnaire score, as rated by teachers, can more accurately predict time discrimination skills than time reproduction, that is the result of cognitive processes that go further beyond the sense of time as assessed by this questionnaire; in line with this observation, the variance explained by the questionnaire scores was low for the time reproduction task.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the profile of sense of time skills as reported by teachers showed a stronger predictive power towards the time discrimination task, and around half of variance of this task was explained by questionnaires’ scores. Time discrimination is considered a less demanding task, in terms of general cognitive skills such as working memory and speed processing, and seems to be a more ‘pure’ measure of time processing, compared to time reproduction (Droit‐Volet, Wearden, & Zélanti, ). Therefore, it is possible that the Sense of Time Questionnaire score, as rated by teachers, can more accurately predict time discrimination skills than time reproduction, that is the result of cognitive processes that go further beyond the sense of time as assessed by this questionnaire; in line with this observation, the variance explained by the questionnaire scores was low for the time reproduction task.…”
Section: Discussionmentioning
confidence: 99%
“…Th ey found that the diff erent executive functions made different contributions to diff erent timing tasks, but more generally, that performance on diff erent tasks may be dependent on diff erent "general" psychological components (e.g. Droit-Volet, Wearden, & Zélanti, 2015 ), and this might be part of the reason that eff ects of ageing seem to depend on the timing task used.…”
Section: Ageing and Performance On Standard Tasks Of Timingmentioning
confidence: 99%
“…We did not completely rule out a memory difference between the sexes for the results. In both two experiments, all participants reached 100% accuracy in their performance of training 2 phase before starting the test session and standard stimuli were presented five times each at the beginning of each block to prevent participants from forgetting them, which are consistent with numerous previous studies (e.g., Gan et al, 2009; Zhang et al, 2014b; Droit-Volet et al, 2015). However, the former just can suggest that, in some way, there are no difference between subjects’ resolving ability for the standard durations (i.e., 400 and 1600 ms), and the latter can’t discriminate different memory ability for men and women.…”
Section: Discussionmentioning
confidence: 59%
“…From one point of view, according to the models of scalar expectancy theory, temporal information processing consists of several cognitive stages, including precise internal clock, memory, and decision process (Gibbon et al, 1984; Rubia and Smith, 2004), which could mean that the categories of cognitive resources (e.g., attention, working memory, updating and inhibition) required by various temporal tasks exist inherent differences because of their specific details (Gil and Droit-Volet, 2011b; Droit-Volet et al, 2015). For instance, some studies emphasized that memory process might play a very limited role in the bisection task because participants could create new reference standards of “Short” and “Long” during the continuous comparison between probe stimuli and original standards (Allan, 2002; Droit-Volet and Rattat, 2007), while this memory capacity is very important to the temporal reproduction task in the same situation (Droit-Volet et al, 2015). Thus, multifarious performances could be observed in previous studies even if the researcher employed the same stimulus material (Gil and Droit-Volet, 2011b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation